2018
DOI: 10.6007/ijarbss/v8-i3/3905
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Foreign Direct Investment on Unemployment rate in Nigeria (1980-2015)

Abstract: The study examined the impact of foreign direct investment on unemployment rate in Nigeria from 1980 to 2015. The study used two explanatory variables (foreign direct investment and capital formation) and one explained variable (unemployment rate). Test carried out include unit root test, co-integration test, and ordinary least square. The study revealed that: There is negative and insignificant relationship between foreign direct investment and unemployment rate in Nigeria, there is positive and significant r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 1 publication
3
17
0
1
Order By: Relevance
“…The results of the study in the long-term were compatible with some previous studies, such as Johnny et al (2018) which demonstrated that FDI reduces the unemployment rate in Nigeria, and Tegep et al (2019) showed that FDI reduces the unemployment rate at 36 Indonesian provinces. Irpan et al (2018) also illustrated that FDI declines the unemployment rate in Malaysia.…”
Section: -Conclusionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results of the study in the long-term were compatible with some previous studies, such as Johnny et al (2018) which demonstrated that FDI reduces the unemployment rate in Nigeria, and Tegep et al (2019) showed that FDI reduces the unemployment rate at 36 Indonesian provinces. Irpan et al (2018) also illustrated that FDI declines the unemployment rate in Malaysia.…”
Section: -Conclusionsupporting
confidence: 91%
“…These results confirm that the relationship of FDI with unemployment is negative and indirect and FDI cannot explain the change in the unemployment rate without using economic growth and the minimum wages as intermediating variables. Johnny et al (2018) [11] studied the impact of FDI on the unemployment rate in Nigeria from 1980 to 2015. The study revealed that: There is a negative and significant relationship between FDI and the unemployment rate, and there is a positive and significant relationship between capital formation and the unemployment rate.…”
Section: -Literature Reviewmentioning
confidence: 99%
“…Based on their study, the impact of foreign direct investment on the unemployment rate in Nigeria from 1980 to 2015, findings from the co-integration test and ordinary least square approach revealed a negative and insignificant relationship between foreign direct investment and unemployment rate. Chella and Phiri (2017) agreed with Johnny et al(2018), when similar study was conducted on South Africa. The outcomes of ARDL approach indicated that FDI had no significant influence on the unemployment reduction except domestic investment which had a significant positive impact on the employment growth rates.…”
Section: Literature Reviewsupporting
confidence: 59%
“…One leading key factor receiving an interesting attention is the effect of either trade openness on unemployment or financial openness (FDI) on unemployment. Studies like Onanuga et al (2018), Johnny et al (2018). Daly (2017), Adamu et al (2017), Matthew and Ogunlusi (2017), Awad et al (2016) are among the few empirical studies that have conducted nexus either between trade openness and unemployment or financial openness and unemployment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Investasi asing (foreign direct investment/FDI) adalah salah satu komponen kunci dari sistem ekonomi internasional yang terbuka dan efisien. FDI adalah investasi langsung yang dilakukan oleh individu atau perusahaan di negara lain untuk kepentingan produksi atau bisnis, baik dengan secara langsung membangun bisnis atau memperluas operasi bisnis yang sudah ada atau dengan membeli perusahaan di negara sasaran (Johnny, Timipere, & Krokeme, 2018). Untuk membuktikan secara empiris pengaruh FDI terhadap pengangguran diantaranya telah dilakukan oleh Stamatiou dan Dritsakis (2014) yang menggunakan beberapa model ekonometrik untuk mengevaluasi dampak FDI terhadap pengangguran dan pertumbuhan ekonomi di Yunani tahun 1970 hingga 2012.…”
Section: Pendahuluanunclassified